2019
DOI: 10.1186/s12931-019-1136-5
|View full text |Cite
|
Sign up to set email alerts
|

Complement factor C5 inhibition reduces type 2 responses without affecting group 2 innate lymphoid cells in a house dust mite induced murine asthma model

Abstract: Background Complement factor C5 can either aggravate or attenuate the T-helper type 2 (T H 2) immune response and airway hyperresponsiveness (AHR) in murine models of allergic asthma. The effect of C5 during the effector phase of allergen-induced asthma is ill-defined. Objectives We aimed to determine the effect of C5 blockade during the effector phase on the pulmonary T H 2 response and AHR in a house dust mite (HDM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…Surface CD40 secreted IL-4, IL-13, IL-21 [36,39] Induction of B cell ε-germline transcription, differentiation and affinity maturation and sIgE production [39,41] Decreased circulating numbers [38,83] Restored [74] Antigen presentation [74] Reduced activation (157)…”
Section: Effect Of Ait On T H 2 and T Fh Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Surface CD40 secreted IL-4, IL-13, IL-21 [36,39] Induction of B cell ε-germline transcription, differentiation and affinity maturation and sIgE production [39,41] Decreased circulating numbers [38,83] Restored [74] Antigen presentation [74] Reduced activation (157)…”
Section: Effect Of Ait On T H 2 and T Fh Cellsmentioning
confidence: 99%
“…Moreover, a study on birch pollen-allergic peripheral blood neutrophils demonstrated their capability to fully process and present the allergen subsequently promoting Bet v 1-specific T cell proliferation and cytokine production [ 73 •]. In a HDM-sensitized murine asthma model, inhibition of the complement component C5a was shown to reduce T H 2 infiltration and IL-4 concentration in the lung tissue without affecting their counterparts ILC2s, suggesting it has a role in amplifying type 2 inflammation [ 74 ].…”
Section: Mechanisms Of Allergic Rhinitismentioning
confidence: 99%
“…In preclinical models, systemic blockade of C5 using the same mAb led to alleviation of bronchoconstriction when ovalbumin induced respiratory inflammation was established [27] and to a reduction on airway resistance without effect on leukocyte numbers in bronchoalveolar lavage fluids in response to house dust mite induced airway hypersensitivity [28]. Joint intranasal and intraperitoneal administrations of C3aR antagonist and anti-C5aR mAb led to a significant reduction of IL-4 in the bronchoalveolar lavage fluids of Aspergillus fumigatus stimulated mice [16].…”
Section: Pathogenesis Driven Treatmentmentioning
confidence: 99%
“…The inflammatory action of ILC2s in HDM‐induced asthma requires Th2 cells 231 . The complement component C5 increases in BALF during HDM‐induced allergic asthma, which increases airway hyperresponsiveness and Th2 cell differentiation without affecting ILC2s 232 . The anti‐C5a therapy decreases the proportion of Th2 cells recruited to the lungs and attenuates the IL‐4 release without impacting the eosinophil and neutrophil influx 232 .…”
Section: Ilc and T Cell Cross‐talk During Allergic Asthma And Other Cmentioning
confidence: 99%
“…The complement component C5 increases in BALF during HDM‐induced allergic asthma, which increases airway hyperresponsiveness and Th2 cell differentiation without affecting ILC2s 232 . The anti‐C5a therapy decreases the proportion of Th2 cells recruited to the lungs and attenuates the IL‐4 release without impacting the eosinophil and neutrophil influx 232 . Due to the expression of IL‐25R or IL17RB and ST2 (IL‐33R), ILC2s produce IL‐13 (increases mucus production) and IL‐5 (recruits eosinophils) in response to IL‐25 and IL‐33, causing allergic asthma 230,233,234 .…”
Section: Ilc and T Cell Cross‐talk During Allergic Asthma And Other Cmentioning
confidence: 99%